Human intraoral myiasis (Research, Society and Development, 2021)
Introduction: Myiasis, a pathological condition in which dipteran larvae infect and parasitise a host, usually occurs in tropical and subtropical climate countries. Larvae can infect different parts of the human body. Intraoral human myiasis is considered a rare condition that is associated with systemic, local and environmental predisposing factors. Objective and case report: This case report describes a systemically compromised patient with expressive intraoral infestation causing pain, bleeding and tissue necrosis. The patient was treated in a hospital environment under the effects of general anaesthesia. Treatment consisted of removal of the larvae, surgical debridement and use of ivermectin. Final considerations: The control of hygiene conditions by the family/caregivers and dental care are determinant for the prevention of intraoral human myiasis, especially in patients with defective self-care presenting with dentofacial skeletal alterations that make normal mouth closure impossible. The control of the disease is a determinant to avoid potential complications, such as airway involvement, secondary infections and sepsis.